Impact of Vanilla Sector Degradation on Socioeconomic in Rural Madagascar - Ralainirina Razokiny Eric; Ralaivao Hanginiaina Emynorane; Jean Tsitaire Arrive (Ite Ngabdi, 2025)
This study examines the economic impacts of vanilla sector degradation in rural Madagascar, with the primary aim of understanding how market instability and environmental stress affect smallholder livelihoods. The study uses a qualitative dominant mixed approach, combining household surveys, semi-structured interviews, and group discussions conducted with 20 participants drawn from major vanilla producing communities. The findings show that heavy dependence on vanilla income exposes households to pronounced vulnerability during periods of price decline, leading to reduced food security, increased labor pressure, and unstable land use practices. These impacts interact and reinforce one another, extending the consequences of sector degradation beyond income loss alone. The study demonstrates that degradation of the vanilla sector generates multidimensional livelihood risks in rural Madagascar.